Analisis Kesalahan Dalam Penyelesaian Soal Matematika Berbasis Timss Konten Geometri Pada Siswa Kelas VIII Semester Genap SMP Negeri 1 Mojosongo Tahun 2015/2016 - Nurkhasanah, Dewi Suwar; , Prof. Dr. Budi Murtiyasa, M.Kom (2016)
This study aimed to describe the kinds of mistakes in solving math problems based geometry TIMSS and the percentage and the factors that cause errors settlement based on TIMSS math geometry content. This research is a qualitative descriptive. Subjects of this study class VIII D SMPN 1 Mojosongo totaling 26 students. The data collection technique using the test method, interviews, observation, and documentation. Data validation was done by triangulation method by comparing data from the test method, interviews, and documentation. Data analysis techniques performed by stage data reduction, data presentation, verification and conclusion. The results were obtained there are three types of errors made by the students are misconceptions, procedural errors and miscalculations. Errors occurred concept as much as 67.77%, procedural errors occurred as much as 17.27%, and calculation errors as much as 13.95%. Factors that influence students' mistakes them is the lack of understanding of students on the material contained on the matter.